Entrenamiento de la musculatura respiratoria en el entrenamiento de la disfagia. - Andrade Vallejos, Andersson Andres (2024)
Addressing dysphagia through respiratory rehabilitation and strengthening of inspiratory and expiratory muscles is an essential component of a comprehensive treatment plan. Improving muscle function and coordination in the swallowing process improves quality of life for those affected by dysphagia and reduces the risk of respiratory health-related complications. The objective of the research was to analyze the efficiency of respiratory muscle training in the treatment of dysphagia through the collection of scientific literature to inform its effects to the general population, using the scientific review as a basis for communicating its impacts to the population. This study was carried out by means of a literature review, using scientific articles obtained from databases such as PEDro, Scielo, PubMed, Scopus, Elseiver, and Worldwide Science. Initially, 80 scientific articles were selected, and then, after evaluating their methodology using the PEDro scale with a score equal to or higher than six points, 32 were chosen to be part of this study, which consisted of clinical trials that allowed us to demonstrate the importance of respiratory muscle exercise in patients with dysphagia, as well as to show that with the combination of other rehabilitation techniques the positive effects increase considerably. Therefore, the contribution of a rehabilitation program in patients with dysphagia shows not only an improvement in respiratory function, but also a positive impact on fatigue, muscle strength, lung volume, and respiratory flow, crucial factors in the treatment of dysphagia.